Santa Teresa tell us how she reads the Bible - Estévez López, Elisa (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
The aim of this article is to show, with the help of the works of St. Teresa, her passion for the Scripture, the indissoluble link there is between the Word of God and her own experience. Her writings express equally the power of the Word of God in her life. Scripture nourishes her prayer and illuminates her existence and all her spiritual experiences, and these, in turn, enrich the intelligence of the Word. Teresa deeply penetrates the sense of Scripture. Her interpretation is born of experience. It is an existential exegesis, which states that the Word is alive and active in life. With the words of Scripture, Teresa expresses her own deep experience of God and with the Scripture she enters profoundly in the ways of love. She feels too the urgency to communicate the truth of her experience and she encourages others to drink at the well of Scripture, because in it they will meet Christ.
Keywords: Saint Teresa; Sacred Scripture; meditation and contemplation of the God’s Word; spiritual accompaniment; spiritual journey; Biblical characters; Mystical experience and Bible